HUBUNGAN TIPE KEPRIBADIAN DENGAN MOTIVASI BELAJAR MAHASISWA STIKES DIAN HUSADA SEMESTER IIB S1 KEPERAWATAN - Supriani, Anik; Chasanah, Nur (JURNAL KEPERAWATAN BINA SEHAT, 2016)
Abstract.Learning activities for each individual does not always take place fair, can sometimes smooth, sometimes - sometimes not, sometimes can quickly capture what is learned, sometimes difficult. This fact is often found in each student in everyday life. Each individual is not the same. This causes differences in behavior among the study could be due to the type of personality mahasiswa.Penyebabnya students. This study aimed to determine the relationship of personality type with student learning motivation STIKES Dian Husada semester Mojokerto IIB S1 Nursing. This research method is analytical to the design used in this research is to study Korelasional.Hasil Design kerpibadian type most extroverted personality types as much as 21 respondents (67.7%). Motivation motivation are at most by 20 respondents (64.5%). Analysis of the relationship with the personality type of motivation with the Wilcoxon statistical test obtained significant value P = 0.001, meaning there is a relationship. It can be concluded that the motivation to learn can be associated with personality types.Keywords: personality type, learning motivation